Lyophilization of pharmaceuticals: an overview and practical approaches for developing the lyophilization cycle - Seon-Kwang Lee; Eun-Sol Ha; Heejun Park; Ji-Su Jeong; Chang Yell Shin; Jeong-Soo Kim; Seong Hoon Jeong; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2026)

Correction to: Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2019)

Combination of photodynamic therapy (PDT) and anti-tumor immunity in cancer therapy - Hee Sook Hwang; Heejun Shin; Jieun Han; Kun Na (Journal of Pharmaceutical Investigation, 2018)
Photodynamic therapy (PDT) is performed using a photosensitizer and light of specific wavelength in the presence of oxygen to generate singlet oxygen and reactive oxygen species(ROS) in the cancer cells. The accumulated photosensitizers in target sites induce ROS generation upon light activation, then the generated cytotoxic reactive oxygen species lead to tumor cell death via apoptosis or necrosis, and damages the target sites which results tumor destruction. As a consequence, the PDT-mediated cell death is associated with anti-tumor immune response. In this paper, the effects of PDT and immune response on tumors are reviewed. Activation of an immune response regarding the innate and adaptive immune response, interaction with immune cells and tumor cells that associated with antitumor efficacy of PDT are also discussed.